IIUM students' Whatsapp Group Chat: a study on apology sequences used in instant messaging interaction - Ismail, Nurshairah; Abdullah, Nur Nabilah (Kulliyyah of Languages and Management, 2021)
The WhatsApp messenger application serves as one of the unlimited instant messaging in the 21st Century and has been used widely by most students as one of the main platform of communication in the university. This paper aims to study Apology Sequences used in WhatsApp interaction among university students at the Kulliyyah of Languages and Management, International Islamic University Malaysia (IIUM). Apology strategy is considered as a fundamental speech act in a conversation between interlocutors as one way to maintain good relationship (Halimeh, et. al., 2015). The study employed Conversation Analysis (CA) as an approach in investigating the sequential organization of apologies strategies of university students’ WhatsApp group chats. From the data collection of about 40 apology sequences found in the students’ WhatsApp group chat, it was found that the two strategy used by the students in group chats were (1) expression of apology with explanation and (2) an expression of apology with an offer of repair.